2005
DOI: 10.1007/s00259-005-1912-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring SSRI occupancy of SERT using the novel tracer [123I]ADAM: a SPECT validation study

Abstract: Binding of [123I]ADAM to SERT in midbrain can be quantified with a single scan starting 200 min after injection. However, the variability of estimated occupancy values may be too high for critical assessment of occupancy of SERT by SSRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…This finding confirms a previous study on baboons that also found the simplified reference tissue model to underestimate specific binding, with an increasing bias for high-density regions (30). The clinical studies published so far have recommended use of a ratio between specific binding regions and cerebellum that includes time-activity curves from 200 to 360 min after injection, with a total acquisition time of 30-60 min (7,9,10,17). This recommendation is based on comparisons with simplified reference tissue model estimates from data generated by sequential acquisitions at 5.5-7 h after injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding confirms a previous study on baboons that also found the simplified reference tissue model to underestimate specific binding, with an increasing bias for high-density regions (30). The clinical studies published so far have recommended use of a ratio between specific binding regions and cerebellum that includes time-activity curves from 200 to 360 min after injection, with a total acquisition time of 30-60 min (7,9,10,17). This recommendation is based on comparisons with simplified reference tissue model estimates from data generated by sequential acquisitions at 5.5-7 h after injection.…”
Section: Discussionmentioning
confidence: 99%
“…With the sample sizes of 10-44 subjects used in previous 123 I-ADAM imaging studies, only major differences would be detectable. Accordingly, occupancy calculations based on the ratio method have been highly variable (17).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in percent 5-HTT occupancy between the strains are also unlikely to explain the observed differences in behavioral response. In humans, therapeutic doses of citalopram (10-60 mg/day) and other SSRIs result in mean 5-HTT occupancies of approximately 75-80% across doses (Erlandsson et al 2005;Meyer et al 2001). To our knowledge, the relationship between and citalopram plasma levels and 5-HTT occupancy in mice has not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…SPECT investigations were performed about 210 min after tracer application (Klein et al 2004;Erlandsson et al 2005;Sacher et al 2006). A total of 180 frames (60/camera head) were collected using a step and shoot mode.…”
Section: Spectmentioning
confidence: 99%